Efektivitas Media Papan Magnet untuk Peningkatan Kemampuan Mengenal Huruf Konsonan bagi Anak Disabilitas Intelektual Sedang (Single Subject Research Kelas X di SLB Autisma YPPA Bukittinggi) - Saragih, Dita Anggrini; Damri, Damri; Nurhastuti, Nurhastuti; Triswandari, Retno (Indo-MathEdu Intellectuals Journal, 2025)
This research is based on the problem that the researcher found at SLB Autisma YPPA Bukittinggi, where a student with intellectual disabilities is having difficulty recognizing consonant letters. This study aims to help improve the students' ability to recognize consonant letters by utilizing magnetic board media. The researcher employs a quantitative research method with an experimental approach in the form of Single Subject Research (SSR) with A-B design. The data collection technique consists of performance tests, and the data are analyzed visually through graphs. The subject of this research is a student with moderate intellectual disabilities who is in class X at SLB Autisma YPPA Bukittinggi. The research results show that in the baseline condition (A) observed three times, the percentages obtained were consecutively 25%, 25%, and 25%. After being given interventions using magnetic boards in condition (B) for eight observation times, the students experienced an increase in ability with percentages of 37.5%, 50%, 50%, 75%, 75%, 100%, 100%, and 100%. It can be concluded that the use of magnetic board media is effective in improving the ability to recognize consonant letters for children with moderate intellectual disabilities.